2020
DOI: 10.1186/s12871-020-0941-1
|View full text |Cite
|
Sign up to set email alerts
|

The combination of transversus abdominis plane block and rectus sheath block reduced postoperative pain after splenectomy: a randomized trial

Abstract: Background: Splenectomy performed with a curved incision results in severe postoperative pain. The aim of this study was to evaluate the effect of transversus abdominis plane block and rectus sheath block on postoperative pain relief and recovery. Methods: A total of 150 patients were randomized into the control (C), levobupivacaine (L) and levobupivacaine/ morphine (LM) groups. The patients in the C group received only patient-controlled analgesia. The patients in the L and LM groups received transversus abdo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…[1] RSB is performed for umbilical and periumbilical sites and is effective in reducing umbilical incisional pain during and after surgery. [4,5] Moreover, RSB can be used Medicine with abdominal ultrasound because it is associated with fewer complications. [4] At our institution, we perform ultrasound-guided RSB before or after surgery.…”
Section: Introductionmentioning
confidence: 99%
“…[1] RSB is performed for umbilical and periumbilical sites and is effective in reducing umbilical incisional pain during and after surgery. [4,5] Moreover, RSB can be used Medicine with abdominal ultrasound because it is associated with fewer complications. [4] At our institution, we perform ultrasound-guided RSB before or after surgery.…”
Section: Introductionmentioning
confidence: 99%
“… 3 , 4 RSB provides analgesia effect for a midline incision by blocking the 7th to 11th intercostal nerves’ terminal branches within the rectus sheath. 5 Clinical studies have shown efficacy in sparing opioid consumption and accelerating recovery following RSB in laparoscopic surgery, however there are limited data on the quality of recovery after transabdominal midline gynecological surgery. 3 , 4 This randomized controlled study looks forward to bring new ideas for postoperative recovery in this kind of surgery.…”
Section: Introductionmentioning
confidence: 99%